The Mental Health Benefits of Kindness-Oriented Schools: School Kindness is Associated with Increased Belongingness and Well-Being in Filipino High School Students. - Datu, Jesus Alfonso D.; Mateo, Nino Jose; Natale, Silvia (Child Psychiatry & Human Development, 2023)
Prior research has demonstrated the role of kind school climate in students' academic and social-emotional learning outcomes. However, there is sparse literature showing the link of school kindness to mental health functioning. This study examines the association of school kindness with well-being dimensions such as positive emotions and depressive symptoms among 1287 Filipino high school students. It also explored whether school kindness would have indirect effects on well-being via school belongingness. Structural equation modeling via maximum likelihood estimation approach showed that school kindness was linked to higher positive emotions and lower depressive symptoms after controlling for demographic covariates such as age and gender. Further, results of bias-corrected bootstrapping analyses demonstrated that school kindness had indirect effects on positive emotions and depressive symptoms via school belongingness. This research underscores the mental health benefits associated with fostering kindness in school contexts.